Karakteristik Pekerja Emas di Lokasi Kerja di Kecamatan Tallo Kota Makkassar Tahun 2020 - Darliana Darwis; Hasriwiani Habo; Muhammad Ikhtiar (Journal of Muslim Community Health, 2021)
Background: Everyday gold workers have direct contact with mercury. Unhealthy environment and unattention to long-term work safety can put workers and people living near the gold workers' locations are at risk of being exposed to the dangers of mercury. This article aims to describe the characteristics of the gold worker respondents at the location of the gold workers in Tallo District, Makassar City. Methods: Cross-sectional study, with a total of 49 respondents. Univariate analysis was performed to describe the number and frequency of respondent characteristics. Results: The gold workers in Tallo District have the following characteristics; gold workers are dominant at the age of 40-49 years, the most recent education is elementary school education, the majority start working at the age <15 years, working for > 8 hours a day, smoking, using personal protective equipment (PPE), being physically active, and the majority of respodents experienced cough within a working day among the gold workers group. Conclusion: The characteristics of the gold worker respondents in Tallo District are dominated by workers aged >40 and having life-style behaviors that are risky to diseases coused by mercury.